The environmental effects of crop price increases: Nitrogen losses in the U.S. Corn Belt - Hendricks, Nathan P.; Sinnathamby, Sumathy; Douglas-Mankin, Kyle; Smith, Aaron; Sumner, Daniel A.; Earnhart, Dietrich H. (My University, 2014)
High corn prices cause farmers to plant more corn on fields that were planted to corn in the previous year, rather than alternating between corn and soybeans. Cultivating corn after corn requires greater nitrogen fertilizer and some of this nitrogen flows into waterways and causes environmental damage. We estimate the effect of crop prices on nitrogen losses for most fields in Iowa, Illinois, and Indiana using crop data from satellite imagery. Spatial variation in these high-resolution estimates highlights the fact that the environmental effects of agriculture depend not only on what is grown, but also on where and in what sequence it is grown. Our results suggest that the change in corn and soybean prices due to a billion gallons of ethanol production expands the size of the hypoxic zone in the Gulf of Mexico by roughly 30 square miles on average, although there is considerable uncertainty in this estimate.
Citation: Hendricks, N. P., Sinnathamby, S., Douglas-Mankin, K., Smith, A., Sumner, D. A., & Earnhart, D. H. (2014). The environmental effects of crop price increases: Nitrogen losses in the U.S. Corn Belt. Journal of Environmental Economics and Management, 68(3), 507–526. https://doi.org/10.1016/j.jeem.2014.09.002
Keywords: JEL: Q15; JEL: Q53; Crop rotation; Spatial; Water quality; Dynamic panel